The effect of maternal education on offspring's mental health - Daniel Graeber; Daniel D. Schnitzlein (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
We estimate the causal effect of maternal education on the mental health of mother's children in late adolescence and adulthood. Theoretical considerations are ambiguous about a causal effect of maternal education on children's mental health. To identify the causal effect of maternal education, we exploit exogenous variation in maternal years of schooling, caused by a compulsory schooling law reform in West Germany. Based on data from the German Socio-Economic Panel, we find no evidence of a causal protective effect of maternal education on children's mental health. Instead, our empirical results suggest a moderate negative effect of maternal education on the daughters' mental health. We find no effects for the sons. Our investigation of potential mechanisms is consistent with the hypothesis that the negative effect of higher maternal labor supply outweighs the positive effect of an expansion in household resources.
Keywords: I10; I21; I26; J62; 330; mental health; education; compulsory schooling reform; intergenerational mobility